A direct metal-free C2–H functionalization of quinoline N-oxides: a highly selective amination and alkylation strategy towards 2-substituted quinolines. Issue 8 (19th May 2017) - Bi, Wen-Zhu; Sun, Kai; Qu, Chen; Chen, Xiao-Lan; Qu, Ling-Bo; Zhu, Shao-Hua; Li, Xu; Wu, Hai-Tao; Duan, Li-Kun; Zhao, Yu-Fen
Abstract : An efficient one-pot methodology for C2-selective amination and alkylation of quinoline N -oxides was developed in the presence of diethyl H -phosphonate. Abstract : An efficient one-pot methodology for C2-selective amination and alkylation of quinoline N -oxides towards 2-substituted quinolines was developed, via the reaction of various quinoline N -oxides with ammonia, a large variety of primary and secondary amines, as well as active methylene compounds in the presence of diethyl H -phosphonate and K2 CO3 under metal free conditions at room temperature.